SISTEM INFORMASI PENGGAJIAN BERBASIS WEBSITE PADA PT CIPTA KIYAT ADIJAYA - Abdul Azis Tri Kuncoro; Tri Santoso (Universitas Methodist Indonesia, 2023)
The payroll system at PT Cipta Kiyat Adijaya whose calculations have not been computerized will take a long time and cause difficulties in finding the history of calculating salaries. That is because there are several parameters used such as attendance recap and performance achievement obtained from the realization of the income and expenditure of each project. The distribution of payslips is also worried to be a wrong delivery because it is still being done by sending an email to each employee. This research will design an information system designed with UML, ERD, and interface so that it fits the system's needs. This website built using the PHP programming language so as to create a payroll system that can accommodate data, calculate, and distribute with computerized system. The personnel manager will find it easier to process payroll data accurately and quickly and from an employee perspective, it will be easier to access salary slips and their calculation history.